HEALTH AND SAFETY PRACTICES DURING COVID 19: HOW TO ENSURE WORKPLACE ENVIRONMENT SAFETY AND HEALTH? - Ana Islamiyah Syamila; Globila Nurika (Universitas Fort De Kock, 2021)
AbstractThe COVID 19 pandemic is a challenge in various sectors in the world, one of which is the workplace. The large population of workers in the workplace which can lead to clusters of the spread of COVID-19, requires workplaces to be able to ensure that workers are healthy and safe. This is done to break the chain of spreading COVID-19. Various efforts that have been made by workplaces in various countries were reviewed based on searches through ScienceDirect, Springer, and Google Scholar which were adapted to research questions. COVID-19 has an impact on economic and business instability at the beginning of the pandemic, which is a challenge for the workplace to be able to adapt to these changes. Work from home is one effort that can be done, but not all jobs can be done at home. The workplace makes various efforts so that workers are healthy and safe, including the provision of personal protective equipment, a safe working distance of about 2 meters, workplace disinfection, engineering, redesign of work stations, development of digital technology, administrative control with work shifts, workload adjustment and various trainings that can be done, one of which is psychological support for workers. Every workplace has a challenge to break the chain of the spread of COVID-19, so a control program must be implemented optimally to ensure workers are safe and secure. Keywords: workplaces, health and safety practice, COVID-19